LPS induces IL‐8 expression through TLR4, MyD88, NF‐kappaB and MAPK pathways in human dental pulp stem cells. (12th July 2012) - He, W.; Qu, T.; Yu, Q.; Wang, Z.; Lv, H.; Zhang, J.; Zhao, X.; Wang, P.
Abstract: Aim: To evaluate the effects of lipopolysaccharide (LPS) on interleukin‐8 (IL‐8) and related intracellular signalling pathways in human dental pulp stem cells (hDPSCs). Methodology: Human pulp tissues were isolated from human impacted third molars, and the hDPSCs were cultured and characterized. The effects of LPS on IL‐8 and Toll‐like receptor 4 (TLR4) gene expression in hDPSCs were investigated using real‐time quantitative RT‐PCR and ELISA. Whether TLR4/MyD88/NF‐кB was involved in the LPS‐induced up‐regulation of IL‐8 in hDPSCs was determined using transient transfection, luciferase assay and ELISA. The involvement of MAPKs in the LPS‐induced up‐regulation of IL‐8 in hDPSCs was investigated via transient transfection, luciferase assay, ELISA and western blot. The data were statistically analysed using Student's t ‐test or one‐wayanova followed by the Student–Neumann–Keuls test. Results: Cells exposed to LPS not only displayed an enhanced expression of TLR4 but also showed an elevated IL‐8 gene expression; exposure to LPS also resulted in the induction of IL‐8 gene transcription via promoter activation. The LPS‐induced IL‐8 promoter activation was inhibited through dominant‐negative mutations in TLR4 and MyD88, but not in TLR2. The LPS‐induced IL‐8 protein release was attenuated through the administration of TLR4‐neutralizing antibody or MyD88 inhibitory peptide and a dominant‐negative mutation in IκBα. In contrast, IL‐8 protein release was enhanced through the expression of NF‐κB p65. Treatment with PDTC, TPCK or Bay117082 effectively antagonized LPS‐induced IL‐8 protein release. Moreover, both the promoter activity and the LPS‐induced release of IL‐8 were diminished upon the administration of U0126 and SB203580, but not SP600125. Moreover, the exposure to LPS activated ERK1/2 and p38 MAPK phosphorylation in cells. Conclusions: This study reports the LPS‐mediated transcriptional and post‐translational up‐regulation of IL‐8, which is a process that also involves TLR4, MyD88, NF‐κB and MAPK.